VS STRUCTURES MODELING IN âSCâ OIL AND GAS FIELD USING DIRECT INVERSION OF AMBIENT NOISE TOMOGRAPHY - Sabila Choiri, Zida
Oil and gas remain the main pillars in fulfilling daily energy needs. Oil and gas production is an active activity that can alter subsurface structures. A good understanding of subsurface conditions is expected to prevent undesirable factors. In this research, the Ambient Noise Tomography method is used as an effort to better understand the subsurface. Ambient Noise Tomography, a method based on ambient noise sources that uses surface wave data, is chosen in this research to observe the current subsurface conditions. Based on data processing, dispersion curves were obtained in the period range of 0.2 to 1.5 seconds. Direct inversion data were plotted horizontally and vertically down to a depth of 0.4 km with a shear wave velocity range varying from 0.15 km/s to 0.675 km/s. The vertical results show clear layer boundaries, indicated by color changes representing velocity changes. The possible layers seen in the inversion results from 0 km to 0.4 km in depth are shale, fine to medium sandstone, and medium to coarse sandstone. Shale is found at a depth of 0.1 km and acts as a caprock, while sandstone lies beneath it, at a depth of about 0.2 to 0.4 km, which likely serves as a reservoir. Additionally, this method also successfully revealed syncline and anticline structures.